The Revitalising The Character of Indigenous Counselors in Indonesia Through Integrating the Teachings of Serat Wedhatama: A Hermeneutic Approach - Wahyudi, Amien; Mungin Eddy Wibowo; Mulawarman; Muhammad Japar (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to identify and analyse the ideal character of indigenous counsellors in Indonesia based on moral and spiritual teachings in Serat Wedhatama. Gadamer's hermeneutic approach is used to explore the deep meaning of the Serat Wedhatama text and contextualize it within the framework of modern guidance and counseling. The primary source of Serat Wedhatama was analysed using a qualitative approach, focusing on the reduction process, data presentation, and conclusions. The Miles and Huberman approach was used in the data reduction and presentation process, which allows the identification of the ideal counsellor character based on Serat Wedhatama. The results of the research, based on the analysis of the Serat Wedhatama text, indicate that Characters such as humility, patience, perseverance, compassion, self-awareness, caution, surrender to God, and remembering the afterlife are identified as important attributes of indigenous counsellors. These findings provide a significant contribution to counselling practice in Indonesia, especially in developing a multicultural counselling model that is more relevant to the local cultural context and spiritual values. By combining traditional principles with a modern approach, this study helps build a more holistic and morally grounded counselling model. This research enriches the literature on multicultural guidance and counselling, while offering an alternative indigenous approach that is more appropriate to Indonesian society. Keywords: indigenous counsellor, serat wedhatama, guidance and counselling, gadamer's hermeneutics, spiritual values